2022
DOI: 10.1021/acs.langmuir.1c03304
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Alkaline-Responsive Chitosan@Giant Liposomes through an Ultrasound-Integrated Microfluidic Approach

Abstract: This paper presents the fabrication of an alkaline-responsive drug carrier, chitosan@giant liposome (CS-GL), by using an ultrasound-integrated microfluidic approach. On the microfluidic chip, water/oil/water droplets are first prepared and then move through an area of ultrasonic radiation to improve the regional saturation of organic solvent and accelerate its removal. At the same time, phospholipid molecules in the oil phase of the droplets are efficiently self-assembled into giant liposomes (GLs). Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Determination of U-CMLVs Entrapment Efficiency (EE): Aqueous solution (20,40,60,80, and 100 μg mL −1 ) of 5-FU were prepared sequentially. The peak area of the absorption spectrum for each concentration of the 5-FU solution was measured using high-performance liquid chromatography (HPLC, Agilent 1260).…”
Section: Field-emission Scanning Electron Microscopy (Fe-sem Hitachi ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of U-CMLVs Entrapment Efficiency (EE): Aqueous solution (20,40,60,80, and 100 μg mL −1 ) of 5-FU were prepared sequentially. The peak area of the absorption spectrum for each concentration of the 5-FU solution was measured using high-performance liquid chromatography (HPLC, Agilent 1260).…”
Section: Field-emission Scanning Electron Microscopy (Fe-sem Hitachi ...mentioning
confidence: 99%
“…According to the previous study, under high-frequency ultrasound, for our prepared 1.409 ± 0.021 μm size U-CMLVs, the diameter is > 1 μm and different from the surrounding medium, so its motion is dominated by acoustic radiation force (ARF). [60][61][62] We calculated ARF and chose high-frequency ultrasound (5 MHz, 0.4 W cm −2 ) to irradiate the dressing we constructed to move the U-CMLVs in the Y-Z plane. Compared the 2 mm height U-CMLVs' dressings with and without high-frequency ultrasound irradiation, the results showed that the U-CMLVs from top to bottom would move to the bottom of the dressing after 2 min of high-frequency ultrasound irradiation (Figure 3a,b and Videos S1 and S2, Supporting Information).…”
Section: Performance Test Of the U-cmlvs Hydrogel Dressingmentioning
confidence: 99%